Impact of Amaranthus hypochondriacus in nutrition for rabbits on meat quality - SHEVCHIK, RS; DUDA, YV; GAVRILINA, OG; KUNEVA, LV; SAMOYLUK, HV (Journal of the Hellenic Veterinary Medical Society, 2021)
Unique properties of Amaranthus hypochondriacus have been extensively utilized in the recent time worldwide both in food technologies and husbandry. An intensive growth of Amaranthus hypochondriacus plants has been made in Ukraine there and, respectively, production of foods based on amaranth is growing, however no research on its use for feeding rabbits is available. Therefore, the study aimed to review the impact of Amaranthus hypochondriacus on slaughter features of rabbits, meat quality including those under storage conditions. The California race rabbits of 60 days age were divided into two groups, 28 animals in each. The rabbits in the study group were fed (by adding to the basal diet) with 20% of amaranth oilcake. The rabbits were slaughtered at age of 120 days. The following key features of meat output and quality performance were determined: pH, moisture content, water-holding capacity, cooking losses, protein and cholesterol content as well as change in pH, microorganisms count, and moisture loss percentage during 9-day storage in chilled state. Amaranthus hypochondriacus effect on the rabbit live weight, hot carcass weight, dressing out percentage, percentage ratio of heart, kidney, liver, lung weight to carcass weight, рН, moisture content, water-holding capacity, and meat morphological structure was determined. Reduction in cholesterol level by 15.07% (р < 0.05) in the meat of rabbits that were fed with Amaranthus hypochondriacus was detected. pH and drip loss percentage were not significantly different among the groups in the shelf-life period. However, it was found out that growth of microorganisms in the meat of rabbits that were fed with Amaranthus hypochondriacus was slowed down: microorganisms count was 1.65 and 1.71 (р < 0.05) times lower than in the control group on the 6th and 9th days of storage, accordingly. The low-cholesterol and bacteriostatic effects of amaranth oilcake in the rabbit nutrition may significantly increase dietary properties of rabbit meat. Use of amaranth oilcake for rabbit fattening has great potential and further studies including the mechanism of antibacterial effect of A. hypochondriacus on the rabbit meat are required